1995
DOI: 10.1111/j.1601-0825.1995.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cessation of tobacco use on the incidence of oral mucosal lesions in a 10–yr follow‐up study of 12 212 users

Abstract: OBJECTIVE: To study the effect of cessation of tobacco use on the incidence of lichen planus, leukoplakia and other oral mucosal lesions. DESIGN: A 10–yr cohort study in a rural population of Ernakulam district, Kerala, India. MATERIAL AND METHODS: Some 12 212 tobacco users were interviewed and examined in a basetine survey and re‐examined annually for 10 years. At each examination they were exposed to health educational programs to encourage them to quit their tobacco use. The incidence rates were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 12 publications
(12 reference statements)
3
57
0
4
Order By: Relevance
“…Smoking has also been suggested in the etiology of erythroplakia 19 . Several intervention studies demonstrated significant reduction or disappearance of leukoplakia lesions in patients who quit their tobacco habit 11,15,20 . Consequently, motivation of patients with oral PM lesions to quit smoking was assumed to represent an important element of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has also been suggested in the etiology of erythroplakia 19 . Several intervention studies demonstrated significant reduction or disappearance of leukoplakia lesions in patients who quit their tobacco habit 11,15,20 . Consequently, motivation of patients with oral PM lesions to quit smoking was assumed to represent an important element of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Tobacco control is a multisectoral issue that needs active collaboration of various health professions, departments/ministries, civil society and non-governmental organizations. [5] Although both smokers, [6] and smokeless tobacco users, [7] derive substantial benefits from cessation, few successfully give up tobacco use. In India, only 1.7% were former daily smokers with the highest percentage in Kerala (4.9%) and lowest in Punjab, Chandigarh, and West Bengal (0.2%).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is wide agreement that the form in which chewing tobacco that is used in South Asia is potentially carcinogenic [11]. An intervention aimed at reducing tobacco use in India resulted in lower incidence of oral precancerous lesions in the intervention group [20]. In South Asia chewing tobacco is largely used in paan [11,21].…”
Section: Discussionmentioning
confidence: 99%